2019
DOI: 10.1016/j.pupt.2019.101852
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics and pharmacodynamics of a novel anti-asthmatic drug, XC8, in healthy probands

Abstract: Introduction: XC8 (histamine glutarimide) is a novel agent which targets eosinophilic migration and mast cell degranulation and has shown anti-asthmatic effects in animal studies. Objective: The objective of this placebo-controlled phase 1 study was to assess the safety of oral XC8 and to evaluate its pharmacokinetic and pharmacodynamic properties. Methods: 32 healthy volunteers in three dose-escalation treatment groups (10 mg [n = 8], 50 mg [n = 8] and 200 mg [n = 16]) were randomized in a 3:1 ratio to XC8 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The small molecule drug XC8 (glutarimide derivative) developed by Pharmenterprises LLC was shown to affect the influx of eosinophils into bronchoalveolar lavage (BAL) in a model of lung inflammation or asthma in rats and guinea pigs [ 33 ]. We demonstrated the complete safety of XC8 in healthy probands in phase 1 clinical trial [ 34 ]. In phase 2a trial, we have shown that the treatment of asthma patients with a high levels of blood eosinophils and serum IFN-γ with XC8 led to an improvement in force expiratory volume in 1 s (FEV 1 ) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The small molecule drug XC8 (glutarimide derivative) developed by Pharmenterprises LLC was shown to affect the influx of eosinophils into bronchoalveolar lavage (BAL) in a model of lung inflammation or asthma in rats and guinea pigs [ 33 ]. We demonstrated the complete safety of XC8 in healthy probands in phase 1 clinical trial [ 34 ]. In phase 2a trial, we have shown that the treatment of asthma patients with a high levels of blood eosinophils and serum IFN-γ with XC8 led to an improvement in force expiratory volume in 1 s (FEV 1 ) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we showed that the treatment of mice stimulated with interferon-c (IFNc) with XC8 led to a decrease of neutrophils in the BAL, which correlated with the decrease of C-X-C motif chemokine 10 (CXCL10), known as IFN-c inducible protein (unpublished data). The phase 1 clinical trial of XC8 conducted in Europe in healthy volunteers in three dose-groups (10, 50, and 200 mg) demonstrated its safety [27]. The single and multiple administration of XC8 for up to 14 days demonstrated good tolerability and a favorable safety profile for the dose range 10-200 mg without accumulation.…”
Section: Introductionmentioning
confidence: 99%